2014
DOI: 10.1051/0004-6361/201322071
|View full text |Cite
|
Sign up to set email alerts
|

Ionization toward the high-mass star-forming region NGC 6334 I

Abstract: Context. Ionization plays a central role in the gas-phase chemistry of molecular clouds. Since ions are coupled with magnetic fields, which can in turn counteract gravitational collapse, it is of paramount importance to measure their abundance in star-forming regions. Aims. We use spectral line observations of the high-mass star-forming region NGC 6334 I to derive the abundance of two of the most abundant molecular ions, HCO + and N 2 H + , and consequently, the cosmic ray ionization rate. In addition, the lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Morales Ortiz et al (2014) report optically thick HCO + (6-5) emission for NGC 6334 I and a size of 40 ± 6 for the outer envelope. This suggests that the HCO + (6-5) emission originates predominantly from an optically thick surface (see also Appendix D).…”
Section: Correlation Of Hco + With Object Parametersmentioning
confidence: 97%
“…Morales Ortiz et al (2014) report optically thick HCO + (6-5) emission for NGC 6334 I and a size of 40 ± 6 for the outer envelope. This suggests that the HCO + (6-5) emission originates predominantly from an optically thick surface (see also Appendix D).…”
Section: Correlation Of Hco + With Object Parametersmentioning
confidence: 97%
“…(Caselli et al 1998), empty hexagons (Bialy et al 2022), an empty circle (Maret & Bergin 2007), and an empty pentagon (Fuente et al 2016). Observational estimates in high-mass star-forming regions are shown as stars (Sabatini et al 2020), solid diamonds (de Boisanger et al 1996), empty diamonds (van der Tak et al 2000, empty thin diamonds (Hezareh et al 2008), and solid thin diamonds (Morales Ortiz et al 2014). Observational estimates in circumstellar discs are shown as solid squares (Ceccarelli et al 2004) and in massive hot cores as empty squares (Barger & Garrod 2020).…”
Section: Appendix C: Cosmic-ray Ionisation Rate Estimates: Update Fro...mentioning
confidence: 99%
“…However, since ζ was recorded to have wide range (0.8 × 10 −17 < ζ(in s −1 ) < 2 × 10 −16 ) in different dense cores around massive protostellar objects (e.g. van der Tak and van Dishoeck 2000; Doty et al 2002;Morales Ortiz et al 2014;Kaźmierczak-Barthel et al 2015), we performed some calculations with higher rates, ζ CMM3 ∼ (5 -10) ×ζ ISM , as described in the context below.…”
Section: Chemical Models and Initial Physical Parametersmentioning
confidence: 99%
“…Several studies showed that the CR ionisation rate, ζ, in massive star-forming regions are much higher than the standard value, ζ ISM = 1.3 × 10 −17 s −1 , by 5 -500 times with a preference values (∼ 5 -10)×ζ ISM (e.g. van der Tak and van Dishoeck 2000; Doty et al 2002;Morales Ortiz et al 2014;Kaźmierczak-Barthel et al 2015). In order to investigate the impact of increasing ζ on the chemistry of CMM3, we run models with higher ionisation rates.…”
Section: The Cosmic Ray Ionisation Ratementioning
confidence: 99%